Penggunaan aplikasi Kahoot dalam metode pembelajaran berbasis game terhadap motivasi belajar siswa - Sakdiyah, Halimatus (Maliki Interdisciplinary Journal, 2024)
This study aims to analyze the use of Kahoot as a learning evaluation medium. Teachers use technology as a learning tool to make teaching easier and provide great motivation for students. This research method uses library research (Library Research). Where in the journal everything discusses the advantages and is obtained when students do learning with Game Based Learning in the form of the kahoot application. Based on the results of the study it can be concluded that the use of the kahoot application is called innovative, practical.